2011
DOI: 10.4267/2042/44791
|View full text |Cite
|
Sign up to set email alerts
|

RLN2 and its role in cancer

Abstract: This work is licensed under a Creative Commons Attribution-Noncommercial-No Derivative Works 2.0 France Licence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 154 publications
(202 reference statements)
0
1
0
Order By: Relevance
“…Encouragingly, studies have shown that reducing levels of relaxin and/or its available receptor, RXFP1, in prostate cancer cells reduced metastasis and invasiveness in vitro (Feng et al 2007;Willcox and Summerlee 2010). Silvertown et al first showed that lentivirally-produced B-R13/17K H2 relaxin demonstrated antagonistic properties in in vitro studies and successfully impaired prostate cancer xenografts in vivo (Silvertown et al 2007).…”
Section: Relaxin Antagonistsmentioning
confidence: 99%
“…Encouragingly, studies have shown that reducing levels of relaxin and/or its available receptor, RXFP1, in prostate cancer cells reduced metastasis and invasiveness in vitro (Feng et al 2007;Willcox and Summerlee 2010). Silvertown et al first showed that lentivirally-produced B-R13/17K H2 relaxin demonstrated antagonistic properties in in vitro studies and successfully impaired prostate cancer xenografts in vivo (Silvertown et al 2007).…”
Section: Relaxin Antagonistsmentioning
confidence: 99%